Comunidades Virtuais em Redes Sociais na Internet: uma proposta de estudo - Recuero, Raquel da Cunha (2005)
This paper deals with a model for the study of virtual communities as Internet social networks. It proposes a method of study for these phenomena. It starts from a conceptual definition of virtual communities and the interdisciplinary construction of the concepct of social network. Finally, based on this debate, the proposal is presented.